Natural products and their derivatives: Promising modulators of tumor immunotherapy - Deng, Li‐Juan; Qi, Ming; Li, Nan; Lei, Yu‐He; Zhang, Dong‐Mei; Chen, Jia‐Xu (Journal of leukocyte biology, 2020)
A wealth of evidence supports the role of tumor immunotherapy as a vital therapeutic option in cancer. In recent decades, accumulated studies have revealed the anticancer activities of natural products and their derivatives. Increasing interest has been driven toward finding novel potential modulators of tumor immunotherapy from natural products, a hot research topic worldwide. These works of research mainly focused on natural products, including polyphenols (e.g., curcumin, resveratrol), cardiotonic steroids (e.g., bufalin and digoxin), terpenoids (e.g., paclitaxel and artemisinins), and polysaccharide extracts (e.g., lentinan). Compelling data highlight that natural products have a promising future in tumor immunotherapy. Considering the importance and significance of this topic, we initially discussed the integrated research progress of natural products and their derivatives, including target T cells, macrophages, B cells, NKs, regulatory T cells, myeloid‐derived suppressor cells, inflammatory cytokines and chemokines, immunogenic cell death, and immune checkpoints. Furthermore, these natural compounds inactivate several key pathways, including NF‐κB, PI3K/Akt, MAPK, and JAK/STAT pathways. Here, we performed a deep generalization, analysis, and summarization of the previous achievements, recent progress, and the bottlenecks in the development of natural products as tumor immunotherapy. We expect this review to provide some insight for guiding future research. This review aims to summarize the integrated research progress of natural products (e.g. curcumin) on the tumor immunotherapy and key intracellular pathways.